2024
DOI: 10.3389/fpls.2024.1366108
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic acid accumulation and secretion contribute to the alkali-stress tolerance of halophyte Leymus chinensis

Huan Wang,
Shuting Zhao,
Bo Sun
et al.

Abstract: Leymus chinensis is a dominant halophytic grass in alkalized grasslands of Northeast China. To explore the alkali-tolerance mechanism of L. chinensis, we applied a widely targeted metabolomic approach to analyze metabolic responses of its root exudates, root tissues and leaves under alkali-stress conditions. L. chinensis extensively secreted organic acids, phenolic acids, free fatty acids and other substances having -COOH or phosphate groups when grown under alkali-stress conditions. The buffering capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In P. tenuiflora plants, 75 AISMs with the -COOH group were discovered, including 42 fatty acids, 3 amino acid derivatives, 22 phenolic acids, and 8 organic acids [33]. Our recently published work revealed that halophyte Leymus chinensis responded to alkali stress via the secretion of phenolic acids, free fatty acids, organic acids, and amino acids [36]. However, that study did not apply salt stress treatment, so the root secretion response of L. chinensis to a high pH was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…In P. tenuiflora plants, 75 AISMs with the -COOH group were discovered, including 42 fatty acids, 3 amino acid derivatives, 22 phenolic acids, and 8 organic acids [33]. Our recently published work revealed that halophyte Leymus chinensis responded to alkali stress via the secretion of phenolic acids, free fatty acids, organic acids, and amino acids [36]. However, that study did not apply salt stress treatment, so the root secretion response of L. chinensis to a high pH was not explored.…”
Section: Discussionmentioning
confidence: 99%